Effect of Group‐Based Outpatient Physical Therapy on Function After Total Knee Replacement: Results From a Multicenter Randomized Controlled Trial. Issue 6 (18th May 2020) - Lenguerrand, Erik; Artz, Neil; Marques, Elsa; Sanderson, Emily; Lewis, Kristina; Murray, James; Parwez, Tarique; Bertram, Wendy; Beswick, Andrew D.; Burston, Amanda; Gooberman‐Hill, Rachael; Blom, Ashley W.; et al.
Abstract : Objective: To evaluate the long‐term clinical effectiveness of a novel group‐based outpatient physical therapy (PT) following total knee replacement (TKR). Methods: In this 2‐center, unblinded, superiority, randomized controlled trial, 180 patients on a waiting list for primary TKR due to osteoarthritis were randomized to a 6 session group‐based outpatient PT intervention and usual care (n = 89) or usual care alone (n = 91). The primary outcome was patient‐reported functional ability measured by the Lower Extremity Functional Scale at 12 months postoperative. Secondary outcomes included knee symptoms, depression, anxiety, and satisfaction. Questionnaires were completed preoperatively and at 3, 6, and 12 months postoperatively. Results: The mean difference in function between groups was 4.47 (95% confidence interval [95% CI] 0.20, 8.75; P = 0.04) at 12 months postoperative, favoring the intervention. The mean difference in function between groups decreased over time, from 8.1 points at 3 months (95% CI 3.8, 12.4; P < 0.001) to 5.4 (95% CI 1.1, 9.8; P = 0.015) at 6 months postoperative. There were no clinically relevant differences in any secondary outcomes between groups, although patients in the intervention group were more likely to be satisfied with their PT. No serious adverse events related to the intervention were reported. Conclusion: Supplementing usual care with this group‐based outpatient PT intervention led to improvements in function at 12 months after TKR, although the magnitude of the difference was below the minimum clinically important difference of 9 points. However, patient satisfaction was higher in the intervention group, and there was some evidence of clinically relevant improvements in function at 3 months.